Situación de salud bucal y estado protésico del paciente Edentado bimaxilar que acude a la facultad de odontología De la universidad de Antioquia: un estudio piloto (2012)
ABSTRACT: The main objective of this study was to analyze oral health conditions and denture status of a sample of bimaxillary edentulous patients treated at the adult clinic of Universidad de Antioquia’s School of Dentistry. Methods: this was a descriptive study on 54 patients seeking consultation between 2008 and 2010. The following variables were considered: age, gender, socioeconomic level, education level, frequency of brushing, mouthwash use, mucosa cleansing, nightly removal of prosthesis, presence of stomatitis, ulcers, fibrous increase, porosities, pigmentations, calculi, fractures, lost teeth, dental wear, and level of satisfaction with the prosthetics apparatus. These variables were described by gender and Chi Square tests in order to observe statistical significances. Results: most of the studied population come from lower socioeconomic groups and have low education levels. 48% of this population presented some kind of upper arch stomatitis. 46% of them remove both prostheses at night, with a greater proportion among women (58%). Calculi were the most important finding in terms of denture status, as it occurred in 79% of lower prostheses. Almost 80% of the assessed population was satisfied with the upper denture, while 44% were satisfied with the lower one. Conclusions: the findings suggest lack of care and control of these patients’ situation, as well as deficiencies in terms of hygiene habits on both the mouth and the prosthesis —a situation that does not match the high levels of satisfaction found.